Resilience in Flood Risk Management – A New Communication Tool. (2016) - Batica, Jelena; Gourbesville, Philippe
Abstract: Natural hazards, floods especially nowadays stand as the most frequent one posing huge damages to urban environment and urban communities. The need to reshape existing urban systems and make them able to accept a certain level of disturbance becomes important. Knowing that urban systems have dynamic characteristic and that the changes are visible on daily level regarding new technologies brings a different light to evaluation of flood vulnerability and flood resilience. New trends and more sophisticated assets are not designed to accept disturbance of natural hazards, at least not all of them. This puts evaluation of flood resilience and flood vulnerability as one of focal factors in process of reshaping build environment, reducing vulnerability, preparing urban communities to accept flooding and to create flood friendly environment. Introduction of a new concept to stakeholders stand as a challenge for flood professionals. A developed tool enables evaluation of flood resilience index for whole urban system. Beside the build environment, stakeholders need education and organization. Proposed presentation enables better communication with the key stakeholders. This paper focuses on analysis of urban systems in Europe and in Asia. The method is a research outcome obtained within projects CORFU and PEARL (www.corfu7.eu; http://www.pearl-fp7.eu/ ). The research focuses also on examination of present flood management strategies and their effectiveness in decreasing flood damage and evaluation of flood resilience.